(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
The objective of the research was to design a communication and dissemination strategy, based on social networks, to promote entrepreneurial culture and spirit among Information Systems Engineering students at the School of Computer Science of the National University of Costa Rica. The study worked with a population of first-year students from 2023, from six campuses (Coto, Pérez Zeledón, Nicoya, Liberia, Interuniversitaria-Alajuela and Heredia). Of the 671 enrolled students, 198 participated in the study, with ages between 18 and 37 years, and an average of 23 years. The methodology included four stages: diagnosis, design, development and evaluation, using tools such as surveys, SWOT analysis and focus groups. Data were collected between March and May 2023 through the Lime Survey platform, disseminated through emails and the Telegram channel "Info-estudiantes". The instrument included informed consent, characterization of participants and collection of information on communication tools. The results highlighted the need for a multi-channel approach adapted to the digital profile of students, prioritising platforms such as Facebook and Instagram. An action plan was designed with clear objectives, indicators and a dynamic model, adaptable to technological and generational changes, strengthening the connection with the university ecosystem